PENERAPAN MESIN PENGIRIS SINGKONG PADA INDUSTRI KECIL KRIPIK SINGKONG - IG.A.K. Suriadi; I D. G. A. Subagia; I K. A. Atmika (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2016)
The Negara city is an area that has already quite crowded, shown by the availability of many facilities, sosmall industrial/business group are emerging, one of which is an industry or group of enterprises manufactureof cassava chips